Teledermatology: From Prevention to Diagnosis of Nonmelanoma and Melanoma Skin Cancer - G. Fabbrocini; V. De Vita; F. Pastore; V. D'Arco; C. Mazzella; M. C. Annunziata; S. Cacciapuoti; M. C. Mauriello; A. Monfrecola (International Journal of Telemedicine and Applications)
Telemedicine is a rapidly developing application of clinical medicine where medical information is transferred through interactive audiovisual media for the purpose of consulting remote medical procedures or examinations, reducing the time of consultation for patients. Teledermatology as an application of telemedicine was developed in 1995: it turns out to be a gradually more ordinary mean of delivering dermatologic healthcare worldwide and will almost certainly have a greater medical function in the future. In particular, teledermatology can aid in the prevention and diagnosis of nonmelanoma and melanoma skin cancer; telemedicine and teledermatology offer the opportunity to make available consultations with experts also by long distance. Overall, patients seem to accept teledermatology, considering it as an excellent mean to obtain healthcare, particularly in those areas with no expert dermatologists available. Clinicians have also generally reported affirmative experiences with teledermatology in the skin cancer field. Further studies focusing on cost effectiveness, patient outcomes, and patient and clinician satisfaction will facilitate to delineate the potential of teledermatology as a mean of prevention and diagnosis of nonmelanoma and melanoma skin cancer.